2018
DOI: 10.15639/teflinjournal.v29i2/293-306
|View full text |Cite
|
Sign up to set email alerts
|

Social Media as a Conduit for Teacher Professional Development in the Digital Era: Myths, Promises or Realities?

Abstract: It is generally accepted that effective teacher professional development is critical to effective educational improvements and reforms of any educational institution. However, a conventional form of teacher professional development is constrained by time and space and, more often than not, there is a lack of perpetual support to teachers in the wake of a training program. An alternative way of teacher professional development therefore needs to be sought. This article argues that social media and all its facet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…Moreover, this study further depicts that the use of social media is found to be an instant alternative to carry out interactive online learning. This result is consistent with what have been portrayed by Alberth et al (2018) and Nugroho and Atmojo (2020) that informal digital learning of English beyond classroom could be conducted with the presence of social media such as WhatsApp, YouTube, Instagram, and Facebook.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, this study further depicts that the use of social media is found to be an instant alternative to carry out interactive online learning. This result is consistent with what have been portrayed by Alberth et al (2018) and Nugroho and Atmojo (2020) that informal digital learning of English beyond classroom could be conducted with the presence of social media such as WhatsApp, YouTube, Instagram, and Facebook.…”
Section: Discussionsupporting
confidence: 91%
“…Leaders can also choose to include professional learning, or not, in a teacher's evaluation, and foster an environment in which teachers have time in their weekly teaching schedule to try and reflect on new skills (Jensen et al, 2016). Traditional, formal models of professional learning face constraints of space and time (Lawless & Pellegrino, 2007;Smith, Wilson, & Corbett, 2009) and the lack of continuing support for participants (Alberth, Mursalim, Siam, Suardika, & Ino, 2018). Models of professional learning that bring all teachers in a system together for days at the beginning or end of the school year often are "inadequate, fragmented and superficial" (Thacker, 2015, p. 38) and do not meet the individual needs of the participants (Ball & Cohen, 1999;Borko, 2004;Wei et al, 2009) or are often something "done to teachers" (Carpenter & Morrison, 2018, p. 25) rather than a participatory and collaborative form of learning.…”
Section: Sustained Duration and Leadershipmentioning
confidence: 99%
“…Through that, I learnt many innovative methods, ideas and I gained many activities to incorporate into the real classroom. (Participant 8, Lines 136-139) Especially, these views demonstrates teachers' strong concern to take individual responsibility for their PD "as free agent learners" (Mushayikwa & Lubben, 2009, p. 376), and social networks' contribution for accessing materials, resources and support (Alberth, Mursalim, Siam, Suardika, & Ino, 2018) across time and space (Parsons et al, 2019). Prior research also suggests that social media platform is an effective shared learning space where teachers produce new knowledge and negotiate their individual classroom practices (Dabbagh & Kitsantas, 2012;Doak, 2018;Haworth, 2016;Morgan, 2010;Visser, Evering, & Barrett, 2014).…”
Section: Implication Of Computer-mediated Communication Technologies For Teacher Qualitymentioning
confidence: 99%